The Effect of O2O Retail Service Quality in Supply Chain Management - Bimal Kumar Sett; Bikash Koli Dey; Biswajit Sarkar (Mathematics, 2020)
The present study focuses on a single-vendor, single-buyer supply chain model for a single type of product with upgraded service provided to the buyer by the vendor. Vendors often increase their profit by providing a lower quality of a particular product. In this study, an advanced supply chain model is developed to increase service in the presence of an unreliable vendor and an online-to-offline (O2O) channeling system. The vendor provides lower quality items to the customer, even though they had committed to providing a certain quality product, in order to increase their profit. For more realistic results, demand is considered to be price-, quality-, and service-dependent. To advertise and sell the products, the manufacturer uses an online system, which the buyer also uses to choose and order the product, where the particular product is delivered to the customer by a third (offline) party; that is, the concept of an O2O retail channel is adopted to improve the service level of the supply chain management (SCM). To control the out-of-control state and improve the production quality, investment is used. Contrary to the literature, service is considered to be constrained, which makes the model more realistic. A classical optimization technique is used to solve the model analytically and a two-echelon supply chain model is obtained under the advanced O2O retail channel, along with optimized profit, shipment volume, selling price, ordering cost, service, back-ordered price discount, lead time, and safety factor values. Some numerical examples and a sensitivity analysis of the key parameters are provided, along with graphical representation, in order to validate the model.